Vibrio natriegens as Host for Expression of Multisubunit Membrane Protein Complexes - Schleicher, Lena; Muras, Valentin; Claussen, Björn; Pfannstiel, Jens; Blombach, Bastian; Dibrov, Pavel; Fritz, Günter; Steuber, Julia (Frontiers in Microbiology, 2018)
Escherichia coli is a convenient host for the expression of proteins, but the heterologous production of large membrane protein complexes often is hampered by the lack of specific accessory genes required for membrane insertion or cofactor assembly. In this study we introduce the non-pathogenic and fast-growing Vibrio natriegens as a suitable expression host for membrane-bound proteins from Vibrio cholerae. We achieved production of the primary Na+ pump, the NADH:quinone oxidoreductase (NQR), from V. cholerae in an active state, as indicated by increased overall NADH:quinone oxidoreduction activity of membranes from the transformed V. natriegens, and the sensitivity toward Ag+, a specific inhibitor of the NQR. Complete assembly of V. cholerae NQR expressed in V. natriegens was demonstrated by BN PAGE followed by activity staining. The secondary transport system Mrp from V. cholerae, another membrane-bound multisubunit complex, was also produced in V. natriegens in a functional state, as demonstrated by in vivo Li+ transport. V. natriegens is a promising expression host for the production of membrane protein complexes from Gram-negative pathogens.